Mechanical characterisation and modelling of resistance welding - Van Rymenant, Patrick (Cranfield University, 2011)
Resistance welding is used very extensively in industry for a wide range of applications. Knowledge and measurement of the dynamic characteristics of resistance welding equipment is important in the design of the equipment and in optimization of welding procedures using finite element software. This is especially true for projection welding where accurate measurements of effective lumped mass and damping of the welding head as well as its maximal acceleration and velocity are required for accurate modelling. This thesis describes a new concept where a mechanical model of the welding head is used together with the imposition of a mechanical load step function with simultaneous measurement of resulting head motion to calculate effective lumped mass and damping factor. Two test systems were devised to implement the step function. In the “free fracture test”, a metal or ceramic bar is loaded to its breaking point and resulting welding head velocity is measured. This data allows accurate calculation of machine parameters. The second test uses the explosion of a small metallic element to impose a step function, when the welding current causes the metallic element to explode. The final version of this test “the exploding button test” uses a small cylindrical element fabricated from welding filler wire, with the advantage that both button geometry and material can be controlled. The exploding button test has proved to be very effective, can easily be used for in-situ measurements and avoids the vibrations associated with the free fracture test. These test were applied to evaluate a range of resistance welding machines. Finally, an innovative projection geometry was developed to significantly increase projection weld quality and this design has now been used extensively in industry. The techniques developed in this thesis have been shown to be practical and effective and have enabled much better understanding of machine kinematics. The measurements provide essential data for modelling of projection welding and in guiding the development of resistance welding machines and procedures.